2002
DOI: 10.1200/jco.2002.20.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Inhibitor COL-3 in the Treatment of AIDS-Related Kaposi’s Sarcoma: A Phase I AIDS Malignancy Consortium Study

Abstract: PURPOSE: Matrix metalloproteinases (MMPs) are involved in tumor invasion and metastasis and are overexpressed in Kaposi’s sarcoma (KS) cells. The primary aim was to define the safety and toxicity of the MMP inhibitor COL-3 in patients with AIDS-related KS. Secondary aims were to evaluate tumor response, pharmacokinetics, and changes in blood levels of MMP-2, MMP-9, vascular endothelial growth factor (VEGF), and basic fibroblast growth factor (bFGF). PATIENTS AND METHODS: COL-3 was administered orally once dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 25 publications
5
66
0
Order By: Relevance
“…The pharmacokinetic results of the present study suggest that Col-3 behaves in a dose-proportional manner, and pharmacokinetic parameters reflecting drug exposure were similar to those observed in other clinical trials to date (21,29). In addition, intraindividual variability was moderate; coefficients of variation in AUC 0 -24 values were 25% and 55% on days 1 and 29 at the MTD, respectively.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The pharmacokinetic results of the present study suggest that Col-3 behaves in a dose-proportional manner, and pharmacokinetic parameters reflecting drug exposure were similar to those observed in other clinical trials to date (21,29). In addition, intraindividual variability was moderate; coefficients of variation in AUC 0 -24 values were 25% and 55% on days 1 and 29 at the MTD, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…In a Phase I study performed at the NCI in patients with advanced solid malignancies, cutaneous photosensitivity reactions precluded treatment at Col-3 doses exceeding 70 and 36 mg/m 2 /day in patients who were and were not using prophylactic sunscreen, respectively, and the lower dose was recommended for subsequent disease-directed trials (21). An unacceptably high incidence of severe cutaneous photosensitivity reactions also precluded dose escalation of Col-3 Ͼ25 mg/m 2 /day in a Phase I study of Col-3 in patients with AIDS-related Kaposi's sarcoma performed by the AIDS Malignancy Consortium (29). For the most part, the toxicities in all three of the trials were nearly identical except for a constellation of manifestations that resembled drug-induced systemic lupus erythematosis in the National Cancer Institute study (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetracyclines act on two levels, they suppress the gelatinase expression (Seftor et al, 1998) and directly inhibit gelatinase activity trough a zinc-chelating effect (Sorsa et al, 1998). The tetracycline derivatives have entered clinical trials as MMP-inhibitors (Cianfrocca et al, 2002). Clodronate and other bisphosphonates have been developed to treat bone diseases due to their ability to inhibit bone resorption.…”
Section: Synthetic Gelatinase Inhibitorsmentioning
confidence: 99%
“…Indeed, this was the rationale for phase 1 and 2 trials in KS patients using the MMP inhibitor known as COL-3 (6-demethyl-6-deoxy-4-dedimethylaminotetracycline), a chemically modified tetracycline. 16,17 In these trials, COL-3 was shown to be active and well tolerated in the treatment of AIDS-related KS. This may be partly related to the finding that COL-3 affects MMPs by multiple mechanisms, including inhibition of MMP activation and expression.…”
mentioning
confidence: 99%